Association of Pharmacogenotyping and Patient-Reported Outcomes in Chronic Pain Management - Anna Bollinger; Kurt E. Hersberger; Julia Gianora; Isabelle O. Urdieux; Henriette E. Meyer zu Schwabedissen; Nikki Rommers; Matthias Schwenkglenks; Céline K. Stäuble; Samuel S. Allemann (Health Services Insights)
Background: Chronic pain is a complex condition affecting patients’ health-related quality of life (HRQoL). Pharmacogenetic (PGx) testing offers an approach to personalize pain management by optimizing medication regimens. However, the impact of this approach on measurable patient reported outcomes (PROs) remains unexplored. Objectives: This study evaluated the association of PGx testing on PROs in chronic pain patients and investigated differences between those who received PGx-guided therapy and those who did not, focusing on changes in HRQoL and pain intensity from pre-to-post PGx. Design: An exploratory pre-post analysis was conducted as part of an observational case series assessing the influence of PGx testing and subsequent PGx-guided therapy on PROs in chronic pain patients with drug-related problems under their analgesic regimen. Methods: PROs were assessed in 29 patients pre-PGx (baseline) and post-PGx (follow-up, 4-6 weeks later). HRQoL was measured using the EQ-5D-5L. The EQ index was calculated using the German value set. Pain intensity was determined with the Numeric Rating Scale (NRS). Minimal important difference (MID) threshold was applied for both outcomes. Statistical analyses included Wilcoxon signed-rank tests, chi-square tests, and effect size calculations. Results: The mean EQ index score improved from pre-to-post PGx (0.379 ± 0.420-0.697 ± 0.307, P  < .001, d  = −0.84). Stratification revealed that the PGx-guided therapy group showed significantly greater improvements in HRQoL and NRS compared to the non-PGx guided therapy group ( P  < .01). Among 19 patients who met the MID for the EQ index, 18 had undergone PGx-guided therapy. For NRS, MID was reached in 3 pain intensity categories in the PGx-guided therapy group. Conclusions: HRQoL and pain intensity significantly improved after PGx testing, with potentially clinically relevant results in the PGx-guided therapy group. Due to the observational nature of the study, further controlled studies are required to assess the clinical impact and economic feasibility of PGx-guided therapy.